Worry and anxiety account for unique variance in the relationship between intolerance of uncertainty and depression. Issue 3 (4th May 2019) - Swee, Michaela B.; Olino, Thomas M.; Heimberg, Richard G.
ABSTRACT: The evidence supporting the relationship between intolerance of uncertainty (IU), a cognitive construct well established in the anxiety literature, and depression is mixed. Some research has demonstrated a direct association between IU and depression, whereas other studies suggest that IU is either unrelated or indirectly related to depression through other pathways, including anxiety. The present study aimed to further elucidate the relationship between IU and depression in an undergraduate sample ( N = 221). We posited a model in which worry and anxiety account for unique variance in the association between IU and depression. Results supported this hypothesis. Worry and trait anxiety significantly accounted for unique variance in the relationship between IU and depression. Furthermore, the model that best fit the data included two additional direct paths, from IU to anxiety and from worry to depression, and excluded the direct path from IU to depression. Our findings support the notion that IU and depression are indirectly related through worry and anxiety. Limitations and future directions are discussed.